Visitor Perceptions of Service Quality in Promoting Environmental Sustainability at Umbul Bening Water Park, East Java - Maskur Hadi; I Ketut Budarma; I Ketut Sutama (The Postgraduate School of Tourism Sahid Polytechnic, 2024)
Purpose: This research aims to determine tourists' perceptions regarding service quality based on environmental sustainability and to create a service quality model to support ecological sustainability at the Umbul Bening tourist attraction. Research methods: The research uses a sequential exploratory mix-method, with an accidental sampling technique of 322 respondents; quantitative data is processed using SERVQUAL (service quality) and IPA (critical performance analysis), while qualitative data processing is analyzed using FGD (focus group discussion). Results and discussion: The research results show that tourists' perceptions of service quality based on environmental sustainability are not good, with a gap in service quality, especially related to environmental quality. Implication: The service model referring to servicescape is an alternative for creating environmental quality in providing services using the SOR (stimulus, organism, response) paradigm approach, which is expected to be able to influence employee consistency in carrying out their work to support environmental sustainability.